Signaling and scheduling at network elements for guaranteed QoS internet - Tang, Peng. (2010)
Due to the emerging needs for Quality of Service (QoS) guarantees in the Next Generation Internet, this report introduced a new QoS provisioning mechanism – Scalable MultiServ, which is inspired from the original Multiservice (MultiServ) Mechanism, to provide a deterministic QoS guarantee to specific customers. Scalable MultiServ (SMS) mechanism will solve the scalability problem and out-of-order packet problem presented in MultiServ by implementing Distributed-FDPS algorithm. Based on Flow-state-dependent Dynamic Priority Scheduling (FDPS) algorithm, Distributed-FDPS proposes a novel Enhanced Dual Token Bucket (EDTB) structure at the traffic source. By means of flow classification, admission control and resource reservation function of Bandwidth Broker, Scalable MultiServ that provides additional functionalities improves scalability and eliminates out-of-order packets. The structure of Scalable MultiServ mechanism and Distributed-FDPS algorithm will be introduced in this report and NS-2 simulation will be used to validate their performance. To support the signaling needs in our Scalable MultiServ framework, a simple signaling model is designed and presented in this report after reviewing various kinds of signaling protocols.